The Mechanism of Good Corporate Governance, Company Size, and Leverage on The Value of Indonesian State-Owned Enterprises - Cantika, Arinda; Darto, Darto (Institut Teknologi dan Bisnis Asia Malang, 2025)
Business growth is currently increasingly rapid and this includes the role of economics, social politics and technological progress. The existence of developments in the economy in Indonesia is proven by the increasing number of companies listed on the Indonesian Stock Exchange (BEI). The purpose of this study was to determine and analyze the effect of Independent Board of Commissioners, Institutional Ownership, Audit Committee, Company Size, and Leverage to Firm Value in BUMN companies in Indonesia. The research method used in this study is panel data regression analysis, with purposive sampling method, the research sample is 16 BUMN companies BUMN companies on the Indonesia Stock Exchange for the 2018-2022 period. The results showed that, in the first model, Independent Board of Commissioners had a negative and insignificant effect, Institutional Ownership had a negative and insignificant effect, Audit Committee had a negative and insignificant effect, Company Size had a positive and significant effect, and Leverage had a positive and significant effect on Firm Value.